ANALISIS PLOT TIME SERIES KOMPONEN NORTH, EAST, DAN UP STASIUN GNSS CORS GMU1 YANG DIIKATKAN TERHADAP TITIK IKAT GPS REGIONAL DI PULAU JAWA DAN PULAU BALI - Sri Rezki Artini; Fadhila Firdausa; Citra Dewi (PILAR, 2022)
The development of GNSS technology in Indonesia is so rapid along with the development of modern basic control point systems. In this development, control points are used for reference in positioning. The system is known as the CORS (Constinuosly Operating Reference System). At the UGM Yogyakarta Geodetic Engineering campus, the development of the GNSS CORS station which began in 2009 has continued to operate, namely the GNSS CORS GMU1 station. The method used in this study was the method of binding network to eight regional control points using doy 196 data to doy 202 in 2012. Considering the definition of the GNSS GMU station as a reference control point is very important, it is necessary to redefine and daily accuracy North, East and Up of the station. The purpose of this study was to obtain a daily accuracy value from the station. Wrms value for North component was 1.4 mm, East component was 4 mm and Up component was 6.7 mm.